Neurosyphilis with ocular involvement and normal magnetic resonance imaging results affirmed by metagenomic next-generation sequencing - Zhou, Xiaoli; Peng, Shengkun; Song, Tiange; Tie, Dandan; Tao, Xiaoyan; Jiang, Li; Zhang, Jie (Frontiers in Cellular and Infection Microbiology, 2022)
Rapid and accurate identification of pathogenic agent is the key to guide clinicians on diagnosis and medication, especially for intractable diseases, like neurosyphilis. It is extremely challenging for clinicians to diagnose neurosyphilis with no high-sensitive and specific test available. As we all know, the early transmission and immune evasion ability of Treponema pallidum have earned it the title of "stealth pathogen". Neurosyphilis has a complex clinical manifestations including ocular involvement which is infrequent and often overlooked but its neuroimaging may be normal. Therefore, it’s significant to find out a new test which can distinguish Treponema pallidum infection or not immediately. We reviewed all the patients admitted to Sichuan Provincial People’s Hospital between 2021 and 2022, who had ocular involvement and did metagenomic next generation sequencing (mNGS) examination, and found 10 candidates for further analysis. Four patients’ magnetic resonance imaging (MRI) were normal, and three of them met the diagnostic criteria for neurosyphilis confirmed by mNGS in the end. In addition, the results of mNGS from the three patients were further validated using polymerase chain reaction (PCR). Five of the 10 patients had diplopia manifestations; two (20%) experienced abducens nerve palsies, two (20%) had eyelid drooping, and one (10%) had decreased vision. One of the 10 patients (10%) who was HIV positive, and six patients had abnormal MRI results. To our knowledge, Treponema pallidum was detected by mNGS in patients with ocular involvement and normal MRI for the first time. Given this situation, we recommend mNGS as a potential and supplementary tool for diagnosis and differential diagnosis of neurosyphilis.